Application of Waterfall Method In Design Of Web-Based Library Information System Program Case Study at Elementary School Warungnangka Kabupaten Subang - Muhammad Faittullah Akbar; Ahmad Fauzi (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2023)
Management of an effective and representative library information system is a necessity for educational units to use a library information system design not only as a requirement but also as a necessity. Elementary School Warungnangka Kabupaten Subang is the focus of research on building a web-based library information system. The data collection methods used are observation, interviews, and case studies. It can be concluded that library management is still not computerized. The design of this information system is carried out using the waterfall method, with the stages of needs analysis, design, implementation of program code using CodeIgniter, and testing using Blackbox so that all processes are running well and as needed. With this library information system, it can simplify the process of borrowing and returning books, speed up library reports, and create added value for the School Accreditation Visitation Program (BAN SM) and School Quality Fulfillment Program (ANBK). This information system will later be able to make information system updates that have been implemented previously, namely the library information system, which is still manual, into a computerized information system.